Process of donating human milk from the milk bank in the city of Petrolina, PE - Sarah Elisheba Mendes do Carmo Santos Gonçalves; Kaliane Gomes Medeiros; Glória Maria Pinto Coelho (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to analyze the donation of human milk at the Banco de Incentivo e Apoio a Amamentação (BIAMA) (Breastfeeding Incentive and Support Bank) from 2018 to 2020. Methods: normative assessment, descriptive and exploratory character, with a quantitative approach and focus on the Donabedian Model. Study with a locus at BIAMA at Dom Malan Hospital, in the city of Petrolina-PE, based on registrations from the online platform of the Rede Brasileira de Bancos de Leite Humano (Brazilian Network of Human Milk Banks), with data from BIAMA from 2018 to 2020 and field activities. Results: in 2020, there was a decrease in the number of group assistance and medical consultations, in contrast to the increase in nursing consultations. Most of the milk supply comes from the external public, and in 2020 there was a reduction number of donors and in the volume of human milk collected. Conclusions: COVID-19 pandemic had a negative impact on BIAMA activities and on milk donation, however, the use of new means of communication for patient care was observed. Even so, new donor recruitment strategies must be implemented. Regarding the main norms that regulate the operation of Human Milk Banks, most of the items listed are obeyed by BIAMA.